2022
DOI: 10.15386/mpr-2325
|View full text |Cite
|
Sign up to set email alerts
|

Oral fixed drug eruptions to mefenamic acid - adverse drug reaction to over the counter medication taken for menstrual pain

Abstract: The reports on adverse drug reactions(ADR) to self-medication or over-the-counter medication are common across medical literature. However, the occurrence of oral fixed drug eruptions (FDE) to mefenamic acid is unique. We report a case of FDE to a drug obtained over the counter for menstrual pain. The essential findings from history, oral/ dental examination, diagnostic approach, and treatment are briefly discussed along with a note on time and dosing for the oral drug provocation tests. The occurrence of ADR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…1 Palla et al in 2022 also reported such an adverse effect related to the use of mefenamic acid 500mg for 3 days. 31 Although NSAIDs main mechanism for causing oral ulceration is by impairing the protective mucosa, it may also cause disturbances in nitric oxide generation and delay soft tissue repair. 32 The differences in gender showed statistical significance (p 0.02) in the occurrence of oral side effects related to the use of NSAIDs, as the cardinal side effects of gingival bleeding and gingival recession was most commonly presented in the female users of NSAID rather than in the males, while inversely, Xerostomia was more common in males than in females.…”
Section: Discussionmentioning
confidence: 99%
“…1 Palla et al in 2022 also reported such an adverse effect related to the use of mefenamic acid 500mg for 3 days. 31 Although NSAIDs main mechanism for causing oral ulceration is by impairing the protective mucosa, it may also cause disturbances in nitric oxide generation and delay soft tissue repair. 32 The differences in gender showed statistical significance (p 0.02) in the occurrence of oral side effects related to the use of NSAIDs, as the cardinal side effects of gingival bleeding and gingival recession was most commonly presented in the female users of NSAID rather than in the males, while inversely, Xerostomia was more common in males than in females.…”
Section: Discussionmentioning
confidence: 99%